Dynamic Competition Model Perspective on the China–US Trade Dispute: Why Did China Adopt Symmetric Tariffs? - Baoguo Chen; Fengde Chen (Mathematics)
This study investigates the evolutionary mechanisms and equilibrium character-istics of the China–US trade dispute through an improved ecological competition model. By quantifying tariff policies as competition intensity regulators and introducing trade elasticity parameters, we construct a dynamic system that captures the nonlinear feedback between economic rivals. Key findings are as follows. (1) When both nations implement reciprocal tariff measures with similar economic sensitivities, the system converges to a stable equilibrium where bilateral economic outputs stabilize at reduced levels compared to pre-conflict states, provided the product of adjusted competition coefficients remains below critical thresholds. (2) Excessive tariff escalation beyond identifiable tipping points triggers winner-takes-all outcomes, validating the “Thucydides Trap” hypothesis in eco-nomic conflicts. (3) Empirical simulations using 2018–2023 trade data demonstrate that China’s tit-for-tat tariff strategy effectively maintains competitive balance, while domestic market expansion measures (evidenced by a 6.3% average annual growth in China’s do-mestic consumption) significantly mitigate trade diversion effects. The study establishes theoretical connections with optimal tariff theory and strategic trade policy literature while providing policymakers with quantitative tools to assess trade policy impacts. Our find-ings theoretically validate China’s policy combination of calibrated reciprocity and domestic demand stimulation, offering new insights into managing great-power economic competition.